INTERNALISASI NILAI-NILAI PANCASILA DALAM MENINGKATKAN KESADARAN BELA NEGARA PADA GENERASI MILENIAL - Shabika Azzaria (Fakultas Syariah dan Hukum Islam Institut Agama Islam Negeri (IAIN) Parepare, 2021)
Abstract At this time the life of the Indonesian people has undergone many shifts due to the influence of globalization. With the shifting changes in this era of globalization, it presents a challenge for the Indonesian people to continue to open up and follow the flow of change, both ready and unprepared. In the current era of globalization, the role of Pancasila is certainly very important in order to maintain the existence of the personality of the Indonesian people, because the influence of globalization of boundaries between countries seems invisible, so that various foreign cultures easily enter into society. The main problem in this research is to internalize the values of Pancasila in increasing awareness of defending the state in the millennial generation and efforts to internalize the values of Pancasila in increasing awareness of defending the country in the millennial generation. In this study, researchers used data collection techniques, namely interviews by sending draft questions via email to lawyers at Arsen & Co. Law firm namely Herly Hermawan and supported by literature study using secondary documents. The results of this study, the importance of internalizing the values of Pancasila because Pancasila has a function and position in the nation and state and can increase awareness of defending the state in citizens by practicing Pancasila values in everyday life in order to maintain the existence of the nation and state of Indonesia and strengthen awareness of defending the state in citizens, especially the millennial generation. The development of state defense awareness is given directions to overcome understandings, ideologies, and cultures that are contrary to the personality values possessed by the Indonesian nation and state. The state defense is carried out on an ongoing basis through education, training and socialization so that it can strengthen the foundation for the availability of defense resources. Keywords: Pancasila, State Defense Awareness, Millennial Generation